Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.4049/jimmunol.175.6.4017
|View full text |Cite
|
Sign up to set email alerts
|

Pyocyanin and Its Precursor Phenazine-1-Carboxylic Acid Increase IL-8 and Intercellular Adhesion Molecule-1 Expression in Human Airway Epithelial Cells by Oxidant-Dependent Mechanisms

Abstract: Pseudomonas aeruginosa secretes numerous factors that alter host cell function and may contribute to disease pathogenesis. Among recognized virulence factors is the redox-active phenazine pyocyanin. We have recently demonstrated that the precursor for pyocyanin, phenazine-1-carboxylic acid (PCA), increases oxidant formation and alters gene expression in human airway epithelial cells. We report in this work that PCA and pyocyanin increase expression of ICAM-1 both in vivo and in vitro. Moreover, phenazines enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 39 publications
1
61
1
Order By: Relevance
“…Unpublished experiments have shown similar synergism between PYO and TNF␣ in activating NF-B-luciferase (data not shown). 3 Previous experiments showed that 24 h of exposure to PYO elicited similar activation of NF-B in the presence of TNF␣ or IL1␤ (18). Thus, PYO elicited synergistic activation of NF-B in the presence of agonists that activated NF-B.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Unpublished experiments have shown similar synergism between PYO and TNF␣ in activating NF-B-luciferase (data not shown). 3 Previous experiments showed that 24 h of exposure to PYO elicited similar activation of NF-B in the presence of TNF␣ or IL1␤ (18). Thus, PYO elicited synergistic activation of NF-B in the presence of agonists that activated NF-B.…”
Section: Discussionmentioning
confidence: 95%
“…However, even in this condition PYO may be an important modulator of 3 C. Schwarzer and T. E. Machen, unpublished observations. innate immune responses of airway epithelial cells because both neutrophils and macrophages release IL1␤ and TNF␣ and other proinflammatory cytokines that activate NF-B into the ASL, and PYO may then synergize with these to augment responses of the airway epithelia (17,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 PCA also increases oxidant formation and alters the expression of IL-8 (interleukin-8) and ICAM-1 (intercellular adhesion molecule-1) in human airway epithelial cells by oxidant-dependent mechanisms. 27 Compounds 1 and 2 showed antimicrobial activity toward three human pathogenic microorganisms (MIC 50 ¼20 mM against B. subtilis, 5 mM against E. hirae and 5 mM against M. luteus). In previously reported literature, 23 the structural neighbors of compound 1, PCA and PCN, efficiently inhibited the growth of Bacillus cereus (MIC o2 mM), whereas showed only modest antimicrobial activity against M. luteus (MIC 20 mM).…”
Section: Resultsmentioning
confidence: 99%
“…Pyocyanin, a representative pigment produced by P. aeruginosa, targets multiple cellular functions and contributes to acute as well as chronic infections, as it has several effects such as stimulating IL-8 release (Look et al, 2005), depressing host-response and inducing apoptosis in neutrophils (Allen et al, 2005). Pyoverdin is also a virulence marker in this pathogen, it was found that pyoverdin regulates its own secretion and the secretion of other P. aeruginosa virulence factors, such as exotoxin A (Lamont et al, 2002).…”
Section: Discussionmentioning
confidence: 99%